Copper Increases the Cooperative Gating of Rat P2x2a Receptor Channels - Garcia Huidobro-Toro, J; Leiva-Salcedo, D; Riquelme-Pacheco, D (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Background/Objectives: P2X receptor channels are widely expressed in the CNS, where they have multiple functions in health and disease. The rat P2X2a (rP2X2a) receptor channel is modulated by copper, an essential trace element that plays important roles in synaptic modulation and neurodegenerative disorders. Although essential extracellular amino acids that coordinate copper have been identified, the exact mechanism of copper-induced modulation has not been yet elucidated. Methods: We used HEK293T cells expressing rP2X2a channel(s) and performed outside-out single-channel and whole-cell recordings to explore copper’s effects on rP2X2 currents and determine whether this metal can increase the cooperative gating of rP2X2a channel. Results: In whole-cell recordings and in patches containing 2 or 3 rP2X2a channels, copper enhanced the ATP-induced currents, significantly reducing the ATP EC50 and increasing the Hill coefficient. Moreover, copper increased the apparent Po in patches containing two or three channels. By contrast, in patches containing only one rP2X2a channel, we did not observe any significant changes in ATP EC50, the Hill coefficient, or Po. Conclusions: Copper modulates the gating of rP2X2a channels, enhancing interchannel cooperativity without altering single-channel conductance or Po. This novel regulatory mechanism could be relevant for understanding the role of P2X2 channels in physiological and pathological processes. © 2024 by the authors.